Escalation of Military Conflict between India and Pakistan in the Post Lahore Declaration (1999 – 2019): Security Dilemma Perspective - Impiani, Dwi (UI Scholars Hub, 2019)
This paper describes the military conflict escalation between India and Pakistan in the period after 1999 Lahore Declaration. After several major wars, military conflicts between the two countries continued to this day. Previous studies on the India-Pakistan conflict only discussed the causes of this conflict and efforts to resolve conflicts. The studies are divided into three major perspectives, namely; security, domestic politics, and political economy, but none has explained how this military conflict is relatively lasting. Using security dilemma as an analytical framework, this paper will explain the variables of the security dilemma that have contributed to the escalating tensions between India and Pakistan. The security dilemma creates a circumstance where offensive action preferable by both states rather than defensive efforts. The main argument of this paper is that India and Pakistan see each other's behavior -such as the development of military defense capability, nuclear weaponry development, and alliance trends- as threats so that they are always remains in the security dilemma situation.